Knock, knock: Who’s there? Nox1 - Itani, Hana A. (2013)
It has become apparent that major sources of reactive oxygen species (ROS) in mammalian cells are the NADPH oxidases. These multimeric enzymes are composed of membrane bound catalytic subunits, or Nox enzymes and a small docking subunit termed p22phox. Depending on the Nox isoform, cytosolic regulatory subunits also play a role in their activation. There are 7 Nox isoforms. The first identified was Nox2, also termed gp91(phox), which is present in phagocytic cells and is responsible for the oxidative burst. Unlike Nox2, the other Nox enzymes exhibit sustained production of ROS at somewhat lower levels. Their modes of activation differ, as do their cellular distribution. Nox 1-4 are expressed in vascular cells in rodents. Nox 5 has been identified in atherosclerotic lesions of humans but is not expressed in rodents. Stimulation of cells with angiotensin II, cytokines, catecholamines, high glucose, or mechanical stretch promote NADPH oxidase activation, in large part due to recruitment of cytosolic subunits to the membrane subunit, leading to formation of the functional enzyme complex that can transfer electrons molecular oxygen and formation of superoxide (O(2) (·–)).(1) Superoxide serves as a progenitor for other ROS, including hydrogen peroxide (H(2)O(2)), peroxynitrite (OONO(-)), and hypochlorous acid (HOCl(-)). Enhanced activity the NADPH oxidases and increased expression of its subunits occur in many pathological conditions including hypertension, diabetes, atherosclerosis, cardiac hypertrophy and heart failure. Studies of genetically altered mice have shown that deletion of various NADPH oxidase subunits protect against these diseases, while their overexpression promotes pathology.(2-4)